Integrated versus standalone home-based records for reproductive, maternal, newborn, and child health in Nepal: A comparative qualitative study with descriptive quantitative profiling - Sudim Sharma; Anjali Neupane; Dikshya Kandel; Pratibha Chalisay; Sabina Marasini; Budhi Setiawan; Deepak Chandra Bajracharya; Shyam Raj Upreti; Leela Khanal; Haruko Yokote; Chahana Singh; Kshitij Karki (PLoS ONE, 2026)
Background Home-Based Records (HBRs) are personal health documents intended to improve continuity of care and caregiver engagement across reproductive, maternal, newborn, and child health (RMNCH) services. In Nepal, both standalone (sHBR) and integrated (iHBR) models are implemented, yet comparative evidence on their utilization and implementation challenges is limited. This study examined utilization patterns and system-level barriers associated with sHBR in Madhesh Province and iHBR in Koshi Province. Methods We conducted a comparative qualitative study with descriptive quantitative profiling between May 17 and August 27, 2024. A total of 100 semi-structured in-depth interviews were completed with caregivers, health workers, Female Community Health Volunteers, and program managers across two provinces. The study applied “kuragraphy,” an ethnographic approach integrating interviews and field observations to construct contextual case narratives. Socio-demographic data were analyzed descriptively using the statistical package for the social Sciences (SPSS). Informed by the Human Centered Design (HCD) approach, the qualitative data were thematically analyzed in Excel using the Journey to Health and Immunization (JTHI) framework. Results Caregivers widely perceived HBRs as essential documents, primarily for immunization tracking and future service access. The iHBR was viewed as more comprehensive and user-friendly, particularly due to its illustrations, which improved comprehension among low-literacy users. However, understanding remained limited among illiterate and marginalized populations. Family involvement in record management was minimal and largely confined to mothers. Implementation barriers included inadequate training – particularly for iHBR use, limited decision-making authority among frontline health workers, incomplete documentation of non-immunization components, poor material quality of sHBR, and concerns regarding the sustainability of donor-supported iHBR initiatives. Conclusion HBR utilization in Nepal is shaped by caregiver literacy, gender dynamics, and health-system readiness. Strengthening training, supportive supervision, user-centered design, and sustainable supply mechanisms will be essential to optimize HBR effectiveness and support equitable RMNCH service delivery.